BUSINESS DEVELOPMENT STRATEGY DESIGN USING TRIPLE LAYERED BUSINESS MODEL CANVAS (DESCRIPTIVE STUDY ON MDC COFFEE HOUSE) - Pane, Vivi Andriani; Sirait, Tongam; Ramauli, Juliana (International Journal of Social Service and Research, 2024)
This study aims to design the right strategy for MDC Coffee House in business development using the Triple Layered Business Model Canvas (TLBMC), as well as identify and analyze the key factors that support its sustainable business strategy. This study uses a qualitative approach to explore sustainable business strategies for the company, focusing on owners, employees, suppliers, and buyers. The results show that the use of TLBMC allows the company to design a more scientific and measurable business strategy, respond to market demands that are increasingly concerned about environmental and social issues, and strengthen its position as a leader in the sustainable coffee industry in Indonesia.